Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran IPA Materi Persilangan Melalui Metode Saintifik di Kelas IX SMP Negeri 19 Kota Bogor - Mulyawati, Eti (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
IMPROVING STUDENT LEARNING OUTCOMES IN SCIENCE SUBJECTS CROSSING MATERIALS THROUGH THE SCIENTIFIC METHOD IN GRADE IX JUNIOR HIGH SCHOOLS (SMP NEGERI 19 KOTA BOGOR) Abstract. The purpose of this study was to find out the increase in student learning outcomes regarding the material for Crossing Science subjects in class IX Junior High Schools (SMP Negeri 19) Bogor City in the odd semester of the 2022/2023 academic year through the use of the Scientific Method. The method used is a class action research method consisting of two cycles. In the first cycle, learning was carried out using the scientific method, while in the second cycle, the scientific method was refined. In each cycle consists of four stages of research namely planning, implementation of action, observation, and reflection. The research data were analyzed using a comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning outcomes. The results of this study indicate that: First, the use of the Scientific Method can improve student learning outcomes about Crossing material in natural science subjects. It is proven that the percentage of student learning outcomes has increased from the initial condition the average value of daily tests was 68.03 in cycle I to 76.17 and in cycle II to 80.60 or in the final condition an increase of 17.05% from the initial condition . It is proven that the percentage of students' learning completeness increased from the initial conditions of 68.57% in cycle I and to 91.43% in cycle II or in the final conditions there was an increase of 33.33% from the initial conditions.